Wpływ wielkości zasolenia oraz nacisku gleby na właściwkości retencyjne wybranego superabsorbentu = Effect of soil solution salinity and soil pressure on retention properties of selected superabsorbent - Pora, Ewa; Kaszubkiewicz, Jarosław; Kawałko, Dorota; Cuske, Mateusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main advantage of superabsorbents is the ability to storage solutions. Addition of hydrogel into soil reduces plants stress due to deficiencies of water. Factors such as soil pressure and salinity of soil solution, limited retention by SAPs.
Keywords: superabsorbent; nacisk; zasolenie; pressure; salinity